2023
DOI: 10.1021/acs.langmuir.2c02789
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Size and Shape on the Tolerances for Misalignment and Probabilities for Successful Oriented Attachment of Nanoparticles

Abstract: Oriented attachment (OA) of nanoparticles is an important pathway of crystal growth, but there is a lack of tools to model OA. Here, we present several simple models that relate the probability of achieving OA to basic geometric parameters, such as particle size, shape, and lattice periodicity. A Moire-domain model is applied to understand twist misorientations between parallel surfaces, and it predicts that the range of twist angles yielding perfect OA is inversely related to the width of the contact area. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…OA involves the coalescence of crystallographically oriented discrete particles followed by interfacial elimination. It typically involves three steps: the collision and rotation of adjacent NPs, the attachment of NPs causing the formation of larger particles, and further recrystallization and interface relaxation. ,, As initial NPs usually have rough surfaces and different shapes, the alignment during the first step is not always perfect when two crystals aggregate. Several studies have observed incomplete OA, in which the particles did not fully correct for misalignment during the OA, and the resulting interface consists of GB dislocations. , Molecular dynamics simulations have provided new insights into the dynamics related to OA. Coherent defect-free bonding occurs when the lattices of two nanocrystals join within a critical angle (∼15°), while defects form at the interface when this critical angle is exceeded .…”
mentioning
confidence: 99%
“…OA involves the coalescence of crystallographically oriented discrete particles followed by interfacial elimination. It typically involves three steps: the collision and rotation of adjacent NPs, the attachment of NPs causing the formation of larger particles, and further recrystallization and interface relaxation. ,, As initial NPs usually have rough surfaces and different shapes, the alignment during the first step is not always perfect when two crystals aggregate. Several studies have observed incomplete OA, in which the particles did not fully correct for misalignment during the OA, and the resulting interface consists of GB dislocations. , Molecular dynamics simulations have provided new insights into the dynamics related to OA. Coherent defect-free bonding occurs when the lattices of two nanocrystals join within a critical angle (∼15°), while defects form at the interface when this critical angle is exceeded .…”
mentioning
confidence: 99%